Effects of Fiber Density and Strain Rate on the Mechanical Properties of Electrospun Polycaprolactone Nanofiber Mats - Conte, Adriano A.; Sun, Katie; Hu, Xiao; Beachley, Vince Z. (Frontiers in Chemistry, 2020)
This study examines the effects of electrospun polycaprolactone (PCL) fiber density and strain rate on nanofiber mat mechanical properties. An automated track collection system was employed to control fiber number per mat and promote uniform individual fiber properties regardless of the duration of collection. Fiber density is correlated to the mechanical properties of the nanofiber mats. Young’s modulus was reduced as fiber density increased, from 14,901 MPa for samples electrospun for 30 seconds (717 fibers +/- 345) to 3,615 MPa for samples electrospun for 40 minutes (8,310 fibers +/- 1,904). Ultimate tensile strength (UTS) increased with increasing fiber density, where samples electrospun for 30 seconds resulted in a UTS of 594 MPa while samples electrospun for 40 minutes demonstrated a UTS of 1,250 MPa. An average toughness of 0.239 GJ/m3 was seen in the 30 second group, whereas a toughness of 0.515 GJ/m3 was observed at 40 minutes. The ultimate tensile strain for samples electrospun for 30 seconds was observed to be 0.39 and 0.48 for samples electrospun for 40 minutes. The relationships between UTS, Young’s modulus, toughness, and ultimate tensile strain with increasing fiber density are the result of fiber-fiber interactions which leads to network mesh interactions.